Two new species of the genera Cidariplura Butler, 1879 and Oxaenanus Swinhoe, 1900 from Yunnan, China (Lepidoptera, Erebidae, Herminiinae) - Zhang, Xin-Yu; Han, Hui-Lin (Zootaxa, 2016)
The Herminiinae genus Cidariplura Butler, 1879 is distributed mainly in the Oriental and partially in the Palaearctic regions (Wu & Owada 2013). The characteristic features of the genus are the structure of the labial palpus, and male foretibia without sheath covering tarsus and containing a tuft of long hairs.